Permainan Pemilahan Sampah Menggunakan Construct 3 Di SDN 184 Buahbatu - Ardi Ramdani; Sari Susanti (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
One of the places of education in Bandung, namely the 184 Buahbatu State Elementary School (SDN) needs to instill concern for waste in its students. Concern for the environment at SDN 184 Buahbatu is still lacking when viewed from waste management. For example, the results of students' work using used goods were not found. The culture that considers waste to be a useless material has not been conveyed carefully by teachers, so that all waste is still considered to be disposed of or destroyed. The culture of sorting waste has not been implemented properly due to the low understanding and motivation of every student at the school. The school has not felt the direct benefits of waste segregation. There are no restrictions such as pamphlets warning not to litter, which are also needed to remind school members. The aim of the research was to design and build using Construct 3 waste sorting game application for students at SDN 184 Buahbatu in increasing awareness of the school environment and its surroundings. The game application for sorting waste is made using the ADDIE method with the help of Scirra Construct 3. As a result, through this developed waste sorting game application, teachers can deliver material about sorting carefully. So that students are more motivated to sort waste by type in the school environment.